Penafsiran Alkitab Dari Perspektif Dialog Profetis: Belajar Dari Sejarah - Lukas Jua (Jurnal Ledalero, 2016)
The progress of biblical interpretation today is the fruit of prophetic dialogue, a basic exegetical attitude shown especially since the Reformation, thanks to Martin Luther’s prophetic courage. He brought the Bible back to the centre of the Church’s life and to its function as its highest authority. Moreover, Luther also paved the way for developing historical-critical methods by revising patristic hermeneutics, emphasizing the literal sense over allegorical ones. Because prophetic dialogue was Luther’s basic perspective, much of his exegesis is still valid today. Modern exegetes interpret the Bible from a similar perspective, and as a result their interpretation promotes ecumenism and inter-religious dialogue. One important initiative is Scriptural Reasoning promoted by Jewish, Christian and Muslim exegetes. Keywords: Reform, counter-reform, prophetic dialogue, critical attitude, courage, freedom, truth, authority, humanism, historicalcritical methods, synchronic approach ------------------------------------------------------------------------------------------------------------------------- Penafsiran Alkitab dari Perspektif Dialog Profetis:Belajar dari Sejarah. Kemajuan penafsiran Alkitab sekarang adalah buah dari dialog profetis sebagai sikap dasar yang ditunjukkan oleh para penafsir sejak awal Reformasi berkat keberanian profetis Luther. Dia mengembalikan Alkitab ke tempat sentral kehidupan Gereja dan menjadikannya sebagai otoritas tertinggi. Lebih dari itu, Luther juga membuka jalan bagi perkembangan penafsiran historis kritis, dengan membuat revisi atas hermeneutik patristik, dengan mengutamakan arti literal dari pada arti alegoris. Banyak hasil penelitian masih berlaku sampai sekarang karena sikap dasar dialog profetis ini. Umumnya para ekseget modern menafsir Alkitab menurut perspektif ini, sehingga penafsiran mereka memajukan ekumene, dan dialog antaragama. Salah satu inisiatif penting yang patut disebut Scriptural Reasoning yang digalakkan penafsir Yahudi, Kristen dan Islam. Kata-kata kunci: